Pattern of Antibiotic Use among Hospitalized Patients according to World Health Organization Access, Watch, Reserve (AWaRe) Classification and Bangladesh Medical University Guideline: Findings from a Selected Medical College Hospital in Bangladesh (Journal of Comilla Medical College Teachers' Association, 2025)
Background: Antibiotic therapy is considered a principal component of infectious disease management in healthcare settings. Continuous, indiscriminate, and excessive use of antimicrobial agents promotes the emergence of resistant organisms, which is a global threat today, and also increases healthcare costs.Objective: To assess the pattern of antibiotic use among hospitalized patients according to Bangladesh Medical University (BMU) guideline and World Health Organization (WHO) Access, Watch, Reserve (AWaRe) classification.Methods: An observational descriptive cross-sectional study was carried out in the department of Surgery and department of Gynaecology & Obstetrics of Dhaka Medical College Hospital from January 2022 to December 2022. A total of 300 prescriptions containing antibiotics was consecutively selected. The BMU guideline and WHO AWaRe categorization of antibiotics were used to assess the prescribing practices of physicians.Results: In this study, the majority of prescriptions (68.7%) in the Gynaecology & Obstetrics department involved a combination of two antibiotics. In the Surgery department, most antibiotics (76%) were prescribed using their generic names, and the majority (83.3%) were administered via the parenteral route. Empirical therapy was predominant in the Surgery department, accounting for 78.7% of prescriptions. Cephalosporins were the most frequently prescribed antibiotic group (82%) in the Gynaecology & Obstetrics department. Overall, 57.3% of prescriptions adhered to the BMU antibiotic guidelines, with the highest adherence observed in the Surgery department. Additionally, 61.3% of antibiotics prescribed in the Surgery department belonged to the "Watch" group, according to the WHO AWaRe classification.Conclusion: Most prescriptions adhered to the BMU antibiotic guideline, and a large proportion of antibiotics prescribed belonged to the Watch group of the WHO AWaRe classification.J Com Med Col Teachers’ Asso July 2025; 29(2): 83-88